Pendampingan Pengelolaan Konten Pendidikan dengan LMS Moodle untuk Guru-Guru di SMU Islam Said Naum - Pratiwi, Dian; Sediyono, Agung; Budi Santoso, Gatot; Sari, Syandra; Ichsan Gunawan, Muhammad; Eka Rizky Illahi, Mohammad (Lembaga Dongan Dosen, 2023)
The increasingly rapid development of technology has an impact on changes in learning models, especially in the transition period due to the Covid-19 pandemic. The increasing use of Learning Management Systems (LMS) in schools shows the need for managing educational content to support online and hybrid teaching systems. This is what will then be implemented at one high school in Jakarta in the form of assistance for teachers in managing web content via the Moodle application. This activity was held at Said Naum Islamic High School on April 10 2023, with a session consisting of Introduction to Moodle Concepts, Practical Preparation, 2 (two) Case Studies. Based on the implementation and evaluation of this activity, quite good feedback was obtained from the participants where 70% of the participants assessed that the material presented was able to provide knowledge and skills regarding the Moodle LMS, and 60% of the participants also stated that they would apply the results of the training to build learning content independently.